Effect of use of chia seed flour (Salvia hispanica l.) and carrot flour (Daucus carota l.) at different levels on physico-chemical and organoleptic qualities of chicken sausages - Kartikasari, Lilik Retna; Prastowo, Sigit; Nuhriawangsa, Adi Magna Patridi; Ratriyanto, Adi (Journal of Advanced Veterinary Research, 2026)
The objective of this research was to evaluate the physical, chemical, and organoleptic qualities of chicken sausages with chia seed flour and carrot flour fillers with different substitution levels. The study design used a completely randomized design with 5 treatments and 5 replications and the treatments included 0% chia seed flour and 0% carrot flour (L0), 3% chia seed flour and 0.75% carrot flour (L1), 6% chia seed flour and 1.5% carrot flour (L2), 9% chia seed flour and 2.25% carrot flour (L3), and 12% chia seed flour and 3% carrot flour (L4). The research data were analysed using analysis of variance and if there was a significant effect, it was analysed further using Duncan’s Multiple Range Test. The findings showed that chicken sausages with filler substitution of chia seed flour at 12% and carrot flour up to 3% had a very significant effect (P<0.01) on water, protein, fat, and collagen content. The content of protein, fat, and collagen of chicken sausages increased with the use of 9% chia seed flour and 1.5% (L2) carrot flour compared to the control group. The L2 treatment produced the same physical and organoleptic quality compared to the control. The results of the study concluded that the use of 6% chia seed flour and 1.5% carrot flour can improve chemical quality while maintaining physical and organoleptic quality so that it can be applied to making chicken sausages.